Gestão da informação e do conhecimento aplicada à gestão de produtos não conformes em uma indústria de laminados de alumínio - Mattos, Yago de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The knowledge produced within an organization is valuable. An effective management of this asset, and its integration with other areas, bring significant results to the company. In the aluminum processing market, where a nonconforming product can have different destinations (rework, disposal, recycling, among others), good knowledge and information management contributes to shorter decision-making time. This study was developed in a multinational company that produces aluminum rolled products. The research aimed to improve the efficiency in the management of nonconforming products, establishing new standard procedures for recording and transferring information. After identifying the opportunities, a systematic review of the literature was carried out, culminating in the determination of the three phases of action-research as the methodology to be used. Knowledge Management and Information Management practices were then used in order to generate formalized knowledge through the production of new flowcharts of procedures for processes related to nonconforming products. The application of these new procedures resulted in the improvement of time-related indicators for decision-making related to nonconforming products and the decrease in the number of non-conformity reports waiting for a decision to be made

O conhecimento produzido dentro de uma organização é valioso. Uma gestão eficaz desse ativo e sua integração com outras áreas trazem resultados importantes para a empresa. No mercado de transformados de alumínio, no qual um produto não conforme pode ter diversas destinações (retrabalho, descarte, reciclagem, entre outras), uma boa gestão do conhecimento e da informação contribui para a diminuição do tempo de tomada de decisão. Este trabalho foi desenvolvido em uma empresa multinacional produtora de laminados de alumínio. A pesquisa teve como objetivo principal tornar a gestão de produtos não conforme mais ágil, estabelecendo novos procedimentos padrão de registro e transferência de informação. Após a identificação de oportunidades de atuação, foi realizada uma revisão sistemática da literatura, culminando na determinação das três fases da pesquisa-ação como metodologia a ser empregada. Foram então utilizadas práticas de Gestão do Conhecimento e Gestão da Informação de modo a gerar conhecimento formalizado por meio da produção de novos fluxogramas de procedimentos para processos ligados aos produtos não conformes. A aplicação destes novos procedimentos resultou na melhora de indicadores ligados ao tempo para a tomada de decisão relacionada a produtos não conformes e à diminuição do número de relatórios de não conformidade aguardando uma decisão a ser tomada
Management of information and knowledge applied to the management of non-compliant products in an aluminum rolling industry
Keywords: Gestão do conhecimento; Administração de produtos; Processo decisório; Knowledge management